Residual Effects of Repeatable Composting on Growth, Yield, and Uptake of Phosphorus Brassica Rapa.L Pakcoy - Anis Sholihah; Agus Sugianto (Agricultural Science, 2022)
This study aimed to determine the potential residues of the rice crop from the second planting period, which were fed with a mixture of pistia compost and rice straw of various compositions with the Brassica rapa L. pakcoy. The study used a factorial randomized block design, the first factor was 7 levels divided into 5 compost mixtures and 2 comparison treatments (NPK fertilizer treatment and control) as follows; control, M1 : 100% pistia, M2 : 75% pistia + 25% rice straw, M3 : 50% pistia + 50% rice straw, M4 : 25% pistia + 75% rice straw, M5 : 100% rice straw and M6 : NPK ., and the second factor is the presence or absence of addition of compost in the second rice planting period divided into 2 levels; 1. (+) = addition of compost, 2.(-) = no addition of compost. The results showed that the residue of composting for the second planting period of rice had a positive effect on soil fertility, especially in the repeated addition of compost, which showed a very significant positive priming effect. The highest positive priming effect was shown by the medium of high-quality compost, namely the treatment of 100% pistia (M1+) seen in the growth parameters and yield of Brassica rapa L pakcoy. The increase in growth due to the addition of repeated compost was 5.10% to 14.24%, and an increase in yield was 5.41% to 11.11% in various treatments of mixed compost media. The treatment with repeated addition of compost gave a significant response to the P uptake of Brassica rapa L plants but the treatment without compost (-) showed 36.72% higher than the treatment with the addition of compost (+).